Impact of compassion on voice behavior: A moderated mediation model - Asma Nisar; Ghulam Abid; Natasha Elahi; Muhammad Ahsan Athar; Saira Farooqi (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Employee voice is a constructive and change-oriented communication that aims to improve a situation. In line with conservation of resource theory, our research proposed a moderated mediation model by examining the indirect effect of compassion on voice behavior through the mediating effect of affective commitment, and also examined the conditional effect of managerial support in the mediated relationship of compassion and voice behavior. Data were obtained from employees and their immediate supervisor in the public sector in three times at regular intervals of one week within a 2-month span of time. By using PROCESS macro on an actual sample of employees (300) and supervisors (19), our study found that compassion is positively associated with affective commitment that, in turn, is positively associated with voice behavior. Our study also found that affective commitment mediates the relationship between compassion and voice behavior. Furthermore, managerial support negatively moderates the relationship between affective commitment and voice behavior as well as mediating effect of affective commitment between compassion and voice behavior. The study finding adds to the deeper understanding of the pivotal construct, i.e., voice behavior. In addition to recommendations for more empirical research on voice behavior, theoretical and practical implications are given.
Keywords: 650; affective commitment; compassion; conservation of resources theory; managerial support; voice behavior